The Effect of Work-Life Balance on Mental Health with Job Satisfaction as a Mediator Variable in Employees PT. XYZ (Energy Sector) - Marianggodo, Wahyu Dodi Tri; Lahindah, Laura (Green Publisher Indonesia, 2025)
Work-life balance is increasingly recognized as a strategic component in human resource management, particularly in high-pressure industries such as oil and gas. This study aims to examine the influence of work-life balance on employee mental health, with job satisfaction acting as a mediating variable. The research was conducted among permanent employees of PT. XYZ, who work under rotational schedules and face intensive operational demands. Utilizing a quantitative approach and survey method, data were collected from 100 respondents using standardized instruments: the Work-Life Balance Scale, the Job Satisfaction Survey , the Mental Health Inventory-38 (Veit & Ware, 1983). The data were analyzed using PROCESS Macro Model 4 with bootstrapping procedures. The findings indicate that work-life balance significantly affects mental health, both directly and indirectly through job satisfaction. Job satisfaction is found to be a significant mediator that amplifies the positive effect of work-life balance on psychological stability. These results reinforce the theoretical perspectives of the Job Demands–Resources model and the Broaden-and-Build Theory, highlighting the affective buffering role of job satisfaction in mitigating psychosocial stress. The mediation model accounts for 56.2% of the variance in employee mental health. Practically, this study provides a foundation for organizations to develop work policies that are not only flexible but also attentive to employees’ affective needs. Emphasizing job satisfaction as a mediation pathway opens opportunities for strategic interventions through job design, emotional support systems, and psychological empowerment in the workplace. This research contributes to data-driven human resource policies aimed at creating healthy and sustainable work environments.